Preparation of Poly(Styrene) Grafted Oil Palm Empty Fruit Bunch Fiber and Its Application as a Filler for High Impact Poly(Styrene) Composites - Jamaluddin, Jamarosliza (2005)
Polystyrene (PS) was grafted onto oil palm empty fruit bunch (OPEFB) fiber in aqueous medium using ~202/Fe~in+it iator system. The grafting percentage was found to be dependent on the reaction period and temperature, amounts of the monomer, the initiator and the cocatalyst. The maximum percentage of grafting (of about 200%) was achieved when the reaction was carried out under the following conditions: reaction period; 4 hours, reaction temperature; 65OC, amounts of monomer; 52.27 mmol, amounts of initiator; 6.00 mmol and amounts of cocatalyst; 0.26 mmol. The reaction mechanism for the grafting of styrene onto OPEFB fiber was proposed and proof of grafting was confirmed by scanning electron microscopy (SEM) and Fourier-transform infrared (FT-IR) analysis. The presence of a peak around 3026 cm-' and two peaks between 698 and 755 cm-'in the FTIR of the product provides strong evidence on the presence of poly(styrene) in the product. The effects of grafting on the thermal properties were studied by thermogravimetry analysis (TGA). Preparation of composite samples were carried out by melt blending in Haake plasticorder with rotor speed of 40 rpm at 1 70°C for 10 minutes, and then followed by hot pressing moulding. The tensile properties of high impact polystyrene &IPS) reinforced with OPEFB, OPEFB-g-PS and crude OPEFB-g-PS fiber were studied. By using OPEFB-g-PS and crude OPEFBg- PS as the filler, it was found that the tensile property of the resulting composites was enhanced. The tensile strength of OPEFB-g-PS and crude OPEFB-g-PSIHIPS composites shows marginal increase up to 20% of filler content but decreases with further increase of the filler content. The incorporation of OPEFB fiber considerably improves the young modulus of the composite but is more significant when using OPEFB-g-PS and crude OPEFB-g-PS as the filler in HIPS composite. The elongation at break decreases with the increase of the filler content. The SEM micrograph shows that the interfacial adhesion between the OPEFB-g-PS and crude OPEFB-g-PS fibers with HIPS matrix are considerably improved compared to that of OPEFB fiber-HIPS composites. The water absorption of the composites increases as the filler loading is increased. However, by grafting poly(styrene) onto OPEFB fiber, the hygroscopicity of the composites can be reduced. The thermal stability of OPEFB-g-PSIHIPS and crude OPEFB-g-PSIHIPS composites are improved. Fourier transform infi-ared (FTIR) spectroscopy shows that the hydroxyl group absorption shift to lower wave numbers which indicates that the hydrogen bonding is formed. The study of the effect of adding various amount of the OPEFB-g-PS fiber into OPEFBIHIPS (20:80) composites was also carried out. Incorporation of the OPEFB-g-PS in these composites also improves the tensile strength and young modulus.